The morphological age and weighted evaluation of the neuromuscular qualities of the young player - Congedo, P.; Primo, A.; Arienti, M.; Galli, F.; Gai, A.; Manganiello, P.; Marinoni, D.; Micheletti, E.; Santoro, F.; Ventura, M. (The Sport Journal, 2023)
This study aims to answer some questions concerning the aspects relating to the anthropometric and neuromuscular evaluation of the young football player.